Kinetic and ecotoxicological evaluation of the direct orange 26 dye degradation by Fenton and solar photo-Fenton processes - Santana, Rayany Magali da Rocha; Nascimento, Graziele Elisandra do; Silva, Polyana Karynne de Aguiar; Lucena, Alex Leandro Andrade de; Procópio, Thamara Figueiredo; Napoleão, Thiago Henrique; Duarte, Marta Maria Menezes Bezerra; Napoleão, Daniella Carla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
The presence of color in textile effluents has been studied because of the need for more effective treatments. Therefore, advanced oxidative processes (AOP) have been used in the degradation of dyes, as well as in the conversion of organic matter. This study evaluated the degradation of the direct orange 26 textile dye by Fenton and photo-Fenton processes (with natural solar radiation). A statistical analysis, based on factorial 23 indicated the best working conditions, being: [H2O2] = 100 mg·L-1 and pH 3-4, for both AOP in that the [Fe] = 1 e 5 mg·L-1, for photo-Fenton and Fenton, respectively. The results of the kinetic studies demonstrated a good fit to the nonlinear kinetic model proposed by Chan and Chu, with values of R2 > 0,996 (photo-fenton) and R2 > 0,939 (Fenton). The tests performed to evaluate the chemical oxygen demand indicated conversions of 62.05% (Fenton) and 66.41% (photo-Fenton). Finally, the ecotoxicity study indicated that the post-treatment samples were non-toxic to the bacteria Escherichia coli and Proteus mirabilis but showed growth inhibition for Lactuca sativa (Fenton and photo-Fenton) seeds and for Brassica juncea and Portulaca grandiflora (Fenton).